Verbal and Non-verbal) pictorial) Metaphorical Conceptualization of ‘Anger’ in the Wars of “Haft Khan of Rostam” - Azadeh Sharifi Moghaddam; Fattaneh Sadat Fatemi (مطالعات زبانی و بلاغی)
The present research aims at the metaphorical conceptualization of ‘anger’ in one of the most valuable epic works of Persian based on the cognitive pattern proposed byKövecses. The data wereextracted from the corpus under study as well as from the related drawings. In thefirst stage, the target domains were identified and then they were classified into three categories of anger metaphors. Then, the pictures were investigated regarding the degree of correspondence between verbal and pictorial levels. The results showed metaphors of three types of central (fire), principal (insanity, dangerous animals, burden, trespassing) as well as minor metaphors.Moreover, metaphorical concepts of ‘fire’, ‘dangerous animals/nature’ as well as the orientational metaphors of ‘victory/failure is up/down’ were common in verbal and pictorial corpus. Finally, the analysis prototype scenario revealed the absence of an "anger control" phase, which could indicate that the greater the degree of anger is, the less likely anger control may occur.